2017
DOI: 10.1098/rsif.2017.0021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vortex structures in a cohort of 204 intracranial aneurysms

Abstract: An intracranial aneurysm (IA) is a cerebrovascular pathology that can lead to death or disability if ruptured. Abnormal wall shear stress (WSS) has been associated with IA growth and rupture, but little is known about the underlying flow physics related to rupture-prone IAs. Previous studies, based on analysis of a few aneurysms or partial views of three-dimensional vortex structures, suggest that rupture is associated with complex vortical flow inside IAs. To further elucidate the relevance of vortical flow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
(93 reference statements)
0
25
0
Order By: Relevance
“…11 To better understand the behavior of WSS, gradients of WSS, and OSI, the basic flow physics of aneurysms needs to be investigated. 1 In addition, the flow physics in aneurysms, such as flows involving complex vortical structures (high flow instabilities), 12 complex and unstable core lines, 13 or higher fraction of vortex structures near the wall, 14 can be helpful in identifying the main factors in aneurysm rupture. 12 All of the above hemodynamic parameters require simulations or experiments to be computed.…”
Section: Introductionmentioning
confidence: 99%
“…11 To better understand the behavior of WSS, gradients of WSS, and OSI, the basic flow physics of aneurysms needs to be investigated. 1 In addition, the flow physics in aneurysms, such as flows involving complex vortical structures (high flow instabilities), 12 complex and unstable core lines, 13 or higher fraction of vortex structures near the wall, 14 can be helpful in identifying the main factors in aneurysm rupture. 12 All of the above hemodynamic parameters require simulations or experiments to be computed.…”
Section: Introductionmentioning
confidence: 99%
“…15, 17, 19–21 To gain further insight into the flow dynamics of IAs, the inflow was classified as either Jet Breakdown Mode or Continuous Jet Mode. 22 We also collected and analyzed clinical features, including previous subarachnoid hemorrhage (SAH), hypertension, and IA location (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, it can lead to high risk of rupture due to the disrupted flow pattern. Varble et al (2017) in their studies, found that the ruptured aneurysm had nearly 1.5 times vortex structures near the surface as compared to the unruptured aneurysm. High WSS could prompt matrix metalloproteinase production through smooth muscle cells that will result in internal elastic lamina damage and cell apoptosis (Varble et al 2017).…”
Section: Wall Shear Stress (Wss) Of the Aneurysmmentioning
confidence: 95%
“…Varble et al (2017) in their studies, found that the ruptured aneurysm had nearly 1.5 times vortex structures near the surface as compared to the unruptured aneurysm. High WSS could prompt matrix metalloproteinase production through smooth muscle cells that will result in internal elastic lamina damage and cell apoptosis (Varble et al 2017). Du and LĂź (2017) in their study regarding the growth and rupture of saccular aneurysm mentioned that WSS of around 1.5 Pa is sufficient to induce the degeneration of endothelial cells in the aneurysm wall causing formation of lesion and subsequently could lead to rupture.…”
Section: Wall Shear Stress (Wss) Of the Aneurysmmentioning
confidence: 95%